2020
DOI: 10.1108/ijchm-04-2020-0325
|View full text |Cite
|
Sign up to set email alerts
|

Comparing crisis management practices in the hotel industry between initial and pandemic stages of COVID-19

Abstract: Purpose Given the increasing number of travel restrictions, the COVID-19 outbreak has dealt a crippling blow to the hotel industry, and the crisis management practices supporting the industry needs are changing as the pandemic continues. This study aims to compare how the hotel industry has responded to this crisis at the initial stage and the pandemic stage. Design/methodology/approach Data were collected from hotel managers in Macau in two occasions, namely, early February and early April 2020. Importance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
262
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(282 citation statements)
references
References 46 publications
15
262
1
4
Order By: Relevance
“…When the pandemic enters the chronic stage, the focus moves towards mental health support and the issues about daily activities. As a micro-economy, Macao has suffered a strong economic impact in its gaming [ 23 , 69 ] and hospitality [ 29 , 70 ] industries, while the city has enforced stringent measures in the areas which are comprised of its main income, for instance, closing down casinos, the mandatory quarantine of travelers and the ban of tourists. Many places in the world actually face the same problem.…”
Section: Discussionmentioning
confidence: 99%
“…When the pandemic enters the chronic stage, the focus moves towards mental health support and the issues about daily activities. As a micro-economy, Macao has suffered a strong economic impact in its gaming [ 23 , 69 ] and hospitality [ 29 , 70 ] industries, while the city has enforced stringent measures in the areas which are comprised of its main income, for instance, closing down casinos, the mandatory quarantine of travelers and the ban of tourists. Many places in the world actually face the same problem.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scholars (e.g., Crandall et al, 2010;Ritchie, 2009) propose that, in order to understand and manage a crisis, it is first important to analyze the different response stages involved. Ritchie (2004) proposed three distinct stages: proactive pre-crisis planning, strategy have also suggested that a crisis can be seen as an opportunity for innovation (Wang and Ritchie, 2012); some have proposed reviewing the marketing mix or market segments, using social media, downsizing, simplifying processes, redefining labor needs and skills, and retraining employees (Lai and Wong, 2020;Pappas, 2018).…”
Section: Crisis Managementmentioning
confidence: 99%
“…The foot and mouth disease in the UK (2001) resulted in conference and trip cancellation, which led to unemployment in the leisure and hotel industry with aggregate losses of 4-5 billion US$ (Brown et al, 2017). The ongoing COVID-19 has caused a 71% decline in hotel occupancy in China during February 2020; besides, 150 Hilton hotels stopped their operations (Lai & Wong, 2020).…”
Section: Infectious Diseases and The Leisure And Tourism Industrymentioning
confidence: 99%